Pemekaran Kecamatan dalam Peningkatan Pelayanan Kependudukan (Studi pada Kecamatan Gampengrejo Kabupaten Kediri) - Fitri, Laila Sabeita El (Jurnal Administrasi Publik, 2013)
Abstract:The District Expznsion in Improvement Population Service. The district expansion at Gampengrejo District in Kediri Regency based on  The Law Number 22 in 1999 about Local Governance and then clarified again by  the Ministerial Decision In 2000 Number 4 about The Guidelines of District Formation. The district expansion at Gampengrejo District in Kediri Regency had been implemented because it has a lot of population, total  territory, and the number of villages. District expansion implemented is to give service to society optimally and to give district offices closer to the people. So this thesis describes the implementation of district expansion in order to improve public services and service population after the real location of district. Became the requirement for the implementation of district expansion had been fulfilled accordance with applicable regulation and  increase in service to the population after the implementation of district expansion is the  distance of the village to the district office become  nearly. Keywords: District expansion, Public Service, Population Abstrak: Pemekaran Kecamatan dalam  Peningkatan Pelayanan Kependudukan. Pemekaran Kecamatan Gampengrejo Kabupaten Kediri berpedoman pada Undang-Undang No. 22 Tahun 1999 tentang Pemerintahan Daerah dan kemudian dipertegas kembali dengan Keputusan Menteri Dalam Negeri No. 4 Tahun 2000 tentang Pedoman Pembentukan Kecamatan. Pemekaran Kecamatan Gampengrejo Kabupaten Kediri dilaksanakan karena memiliki jumlah penduduk yang banyak, wilayah yang sangat luas, dan jumlah desa bawahan yang banyak. Pemekaran Kecamatan Gampengrejo dilaksanakan bertujuan untuk dapat memberikan pelayanan kepada masyarakat secara lebih optimal dan lebih mendekatkan kantor kecamatan lebih dekat dengan masyarakat. Tulisan ini mendiskripsikan pelaksanaan pemekaran kecamatan dalam rangka meningkatkan pelayanan kependudukan serta mendiskripsikan peningkatan pelayanan kependudukan setelah adanya pemekaran kecamatan. Syarat untuk pelaksanaan pemekaran kecamatan sudah terpenuhi sesuai dengan peraturan yang berlaku sehingga setelah pelaksanaan pemekaran kecamatan menyebabkan jarak tempuh desa terhadap kantor kecamatan semakin dekat.   Kata kunci: Pemekaran Kecamatan, Pelayanan Publik, Kependudukan